Real-life writing activities, Grades 1-3 : based on favorite picture books - Rothstein, Gloria (New York : Scholastic Professional Books, 2002)
Super fun activities and reproducibles that use picture books as models to help kids practice 11 kinds of real-life writing.
Keywords: Language and literature -- Study and teaching -- Juvenile literature